Formal features of Filipino ESL research papers - Garcia, Miguel Lorenzo B. (Animo Repository, 2020)
This paper investigated the formal and non-formal features of academic writing in 15 research papers (RP) written by Filipino teachers who consider English as an ESL. The framework used is that of Swales and Feak’s (2004) features of academic writing. The frequency and percentage of these features were then obtained by dividing the frequency of informal features by the number of RPs. Some deviations were found in the different sections of the RPs namely Introduction, Method, Results & Discussion and Conclusion. The sections with the most deviations in descending order are the Results and Discussion, Introduction, Method and Conclusion sections. Based on the findings, implications for teaching academic writing were presented in the conclusion.